Rectovaginal fistula after low anterior resection for rectal cancer healed by nonoperative treatment. (2017) - Emoto, Shigenobu; Nozawa, Hiroaki; Yoneyama, Satomi; Murono, Koji; Kaneko, Manabu; Sasaki, Kazuhito; Otani, Kensuke; Nishikawa, Takeshi; Tanaka, Toshiaki; Hata, Keisuke; Kiyomatsu, Tomomichi; Kawai, Kazushige; et al.
Highlights: Rectovaginal fistula (RVF) is one of the complications after low anterior resection for rectal cancer. RVF has been considered to be refractory to conservative treatment. We report a case of RVF in which conservative treatment was successful. Abstract: Background: Rectovaginal fistula (RVF) is a serious complication after colorectal anastomosis using a double-stapling technique. RVF following this procedure has been considered to be refractory to conservative treatment. Case presentation: A 75-year-old woman who underwent laparoscopy-assisted low anterior resection for early rectal cancer developed RVF on the 12th postoperative day. Conservative treatment was chosen and was successful. She was discharged from the hospital after 3 weeks with a normal oral diet. Colonoscopy on the 50th postoperative day showed that the RVF was closed. Conclusion: Conservative treatment may be effective for RVF after colorectal anastomosis using a double-stapling technique when there is no evidence of defecation through the vagina.